Neutron diffraction study of the structural and electronic properties of Sr2HoMn2O7 and Sr2YMn2O7 - Battle, P; Millburn, J; Rosseinsky, M; Spring, L; Vente, J; Radaelli, P (1997)
The crystal structures of Sr2HoMn2O7 and Sr2YMn2O7 have been determined at 290 and 1.7 K from neutron and X-ray powder diffraction data. Both are distorted Ruddlesden-Popper structures formed by the intergrowth of rock-salt-like layers and perovskite-like blocks of tilted MnO6 octahedra (space group P42/mnm; for Ho at 290 Ka = 5.40388(5), c = 19.9050-(2) Å). The majority of the lanthanide cations are located in the rock-salt layers. Neither structure changes significantly on cooling to 1.7 K. There is evidence for neither charge ordering of Mn3+ and Mn4+ cations nor for long-range magnetic ordering. The magnetic susceptibility maximum observed previously is thus confirmed as signifying a transition to a spin-glass phase. The behavior of these compounds is contrasted with that of other Mn oxides which show long-range magnetic order and colossal magnetoresistance.